Genomic Characterization of Picornaviruses Isolated From Ribbon (Histriophoca fasciata) and Harbor (Phoca vitulina) Seals - Rodrigues, Thais C. S.; Nielsen, Ole; Burek-Huntington, Kathy A.; Popov, Vsevolod L.; Raverty, Stephen; Lambourn, Dyanna M.; Subramaniam, Kuttichantran; Waltzek, Thomas B. (Frontiers in Veterinary Science, 2020)
The seal picornavirus 1, species Aquamavirus A, is currently the only recognized member of the genus Aquamavirus within the family Picornaviridae. The bear picornavirus 1 was recently proposed as the second species in the genus under the name aquamavirus B. Herein, we determined the complete genomes of two novel pinniped picornaviruses, the harbor seal picornavirus (HsPV) and the ribbon seal picornavirus (RsPV). The HsPV and the RsPV were isolated in Vero.DogSLAMtag cells from samples collected from stranded harbor (Phoca vitulina) and ribbon (Histriophoca fasciata) seals. RsPV-infected Vero.DogSLAMtag cells displaying extensive cytopathic effects were processed for transmission electron microscopy and revealed non-enveloped viral particles aggregated into paracrystalline arrays in the cytoplasm. A next-generation sequencing approach was used to recover the complete genomes of the HsPV and the RsPV (6,709 bp and 6,683 bp, respectively). Phylogenetic and genetic analyses supported the HsPV and the RsPV as members of the Aquamavirus genus. Based on these results, RsPV represents a novel strain of Aquamavirus A, while the HsPV is a novel strain of the proposed species aquamavirus B. These discoveries provide information on the evolutionary relationships and ultrastructure of aquamaviruses and expands the known host range of those viruses. Our results underscore the importance of the application of classical virology and pathology techniques coupled with high-throughput sequencing technologies for the discovery and characterization of pathogens in wild marine mammals.